Sri Lanka 2024 - Mayhew, Bradley; Francis, Joseph Richard; Paska, Marisa Megan; Perera, Demi; Rathnayake, Zinara; Karunatilaka, Shehan; Cader, Fathima (Lonely Planet guidebooks., 2024)
Discover popular and off the beaten track experiences from reef diving and snorkelling around Pigeon Island, to experiencing Sri Lanka's most iconic train ride through scenic tea plantations, and spotting leopards and sloth bears in the crowd-free Kumana National Park.